Form factors of radiative pion decays in nonlocal chiral quark models - Gomez Dumm, Daniel Alberto (2012)
We study the radiative pion decay π +→e +ν eγ within nonlocal chiral quark models that include wave function renormalization. In this framework we analyze the momentum dependence of the vector form factor F V(q2) and the slope of the axial-vector form factor F A(q2) at threshold. Our results are compared with available experimental information and with the predictions given by the Nambu-Jona-Lasinio model. In addition we calculate the low energy constants δ 5 and δ 6, comparing our results with the values obtained in chiral perturbation theory.